Ignition of Water Coal Particles Coated with a Waterfilm in the Stream of High-Temperature Environment - Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Bugaeva K. Ksenia; Taburchinov R. Roman (2015, 2015)
Title screen